Penerapan Digitalisasi Marketing dalam Meningkatkan Pendapatan UMKM Desa Telajung - MH Ainulyaqin; Adrianna SR; Sukron Mamun; Preatmi Nurastuti; Afifah KA; Widia Salsabilah (JPPI: Jurnal Pengabdian Pelita Insani, 2025)
The implementation of digital marketing has proven its positive impact on Micro, Small, and Medium Enterprises (MSMEs). This case study explores how UMKM Lemon Sereh Bunda in Telajung Village increased the visibility and sales of their products through digital initiatives, such as website creation, active presence on social media, and utilization of e-commerce platforms. By generating engaging and relevant content, this MSME successfully created strong brand awareness, achieved significant sales growth, and had a positive impact on the local economy.